TEACHER’S STRATEGY TO BOOST STUDENTS’ INTEREST IN STUDYING ENGLISH THROUGH ZOOM MEETING APPLICATION AT THE TENTH GRADE OF SMAN 9 MALANG - Fika Noviantica Priyadi (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: During this virtual learning conditions, media is very important to make learning activities in the classroom run optimally with the help of technological innovation such as Zoom Meeting Applications. However, in the pandemic era, learning and teaching must be continued online, in distance learning. This study aims to find out the teacher's strategy in teaching English and to know the factors that influence students' interest in studying English at class X in SMAN 9 Malang. This research used qualitative research and the subject of this research are from both X IPS 1 & X IPS 2 that were 5 students and 1 teacher of SMAN 9 Malang. In investigating students and teacher’s perspective, the researcher used interview as the instrument for collecting data. Furthermore, the questions are adapted from Nurhamidah (2012) and Rindiani (2021) which has been validated. The findings of this study showed the students’ perceptions toward teacher’s strategy were positive. Students said that teacher’s strategy which used discourse strategy by explaining the material at beginning of the study can ease students understanding and increase vocabularies. Unfortunately, most students’ perceptions toward using Zoom Meeting Application were negative which students and teacher got some troubles, such as bad internet connection and underestimating the learning.Keywords: Strategy, interest, zoom meeting application